Home advantage in speed skating: Evidence from individual data - Koning, R. H. (Journal of Sports Sciences, 2005)
Home advantage is a well-documented phenomenon in many sports. Home advantage has been shown to exist for team sports (soccer, hockey, football, baseball, basketball) and for countries organizing sports tournaments like the Olympics and World Cup Soccer. There is also some evidence for home advantage in some individual sports, but there is a much more limited literature. This paper addresses the issue of home advantage in speed skating. From a methodological point of view, it is difficult to identify home advantage, because skaters vary in their abilities and the conditions of tournaments vary. There is a small but significant home advantage using a generalized linear mixed model, with random effects for skaters and fixed effects for skating rinks and seasons. Even though the home advantage effect exists, it is very small when compared to variation in skating times due to differences of rinks and individual abilities.